Transport phenomena modeling of novel renewable natural gas reactors in various configurations. (31st December 2022) - Bolt, Andre; Dincer, Ibrahim; Agelin-Chaab, Martin
Abstract: This paper presents a comparative assessment of several novel synthetic natural gas fixed-bed reactor designs and configurations. The four reactor concepts presented in the paper use the Sabatier reaction between carbon dioxide and hydrogen to produce methane. Due to the exothermic nature of the reaction and its pressure sensitivity, this study emphasizes the ability and potential of the reactor configurations to provide effective cooling, and minimize heat gain and pressure drops, so that the maximum methane yield and carbon dioxide conversion can be achieved. Out of four reactor designs, Concept 1 follows a conventional cylindrical fixed-bed reactor design; however, the bed is separated horizontally to promote inter-cooling. Concept 2 separates the bed into 2 segments vertically to facilitate cooling along the length of the reactor. Concept 3 follows a horizontal configuration in which the catalyst beds are separated into rectangular prisms. The different configurations of Concepts 1 to 3 were designed by varying the reactor dimensions and the number of catalyst beds. Most notably, Concept 4 using a unique helical design provides more effective cooling to the catalyst bed by increasing the surface area and decreasing the diameter of the reactor channel. However, the volumetric flow of this specific reactor model is significantly reduced. Furthermore, the inlet conditions of 200 °C and 30 bar help achieve a CH4 yield of approximately 85 % when considering Concept 1.